2020
DOI: 10.2147/jpr.s283986
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ultrasonography-Guided Radiofrequency Ablation for Painful Stump Neuromas to Relieve Postamputation Pain: A Pilot Study</p>

Abstract: Objective Postamputation pain (PAP) is a serious problem, and thus far, there is no perfect treatment strategy. Clinically, minimally invasive treatments for peripheral neuromas are simple and feasible. This study aimed to investigate the immediate and long-term effects of ultrasonography-guided radiofrequency ablation (RFA) on PAP. Methods Eighteen PAP subjects with painful peripheral neuromas were treated with ultrasonography-guided RFA. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…A possible answer to this question may come from a different ablative technique—the radiofrequency. Several reports on the effect of ablative radiofrequency treatment (where target temperature far above 65°C has been reached) yielded positive results, 7,8,14 congruently with to what we aimed to achieve with the MRgHIFU treatment. However, in at least 1 study in patients with Morton's neuroma, US‐guided pulsed radiofrequency treatment (with only a sub‐ablative temperature of ~42°C rather than true ablative temperature) was administered.…”
Section: Discussionsupporting
confidence: 84%
“…A possible answer to this question may come from a different ablative technique—the radiofrequency. Several reports on the effect of ablative radiofrequency treatment (where target temperature far above 65°C has been reached) yielded positive results, 7,8,14 congruently with to what we aimed to achieve with the MRgHIFU treatment. However, in at least 1 study in patients with Morton's neuroma, US‐guided pulsed radiofrequency treatment (with only a sub‐ablative temperature of ~42°C rather than true ablative temperature) was administered.…”
Section: Discussionsupporting
confidence: 84%
“…Clinically, MRgFUS has potential as a non-invasive alternative to other ablation modalities, including radiofrequency ablation. Peripheral nerve ablation has been studied in a variety of cancerous (8,9,12,13) and non-cancerous conditions (6,10,11). Ablation has also been used to treat tumors with close proximity to neural structures (14).…”
Section: Discussionmentioning
confidence: 99%
“…There is great potential in extending the use of MRgFUS to the peripheral nervous system for treating conditions such as spasticity and chronic pain (6), which is supported by observations of FUS effects on nerve conduction (7). Ablation techniques, of which MRgFUS is a potential alternative, have been studied in peripheral nerve-related conditions including painful stump neuromas (8), peripheral nerve sheath tumors (9), inguinal neuralgia (10), and lumbar degenerative disease (11). Ablation has also been used for cancer pain relief (12,13) and to treat tumors with proximity to neural structures (14).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral sensitization, central sensitization, and cerebral cortical reconstruction have been proposed as possible mechanisms underlying CPAP. However, the responsiveness of CPAP to available painkillers such as the anticonvulsant drug gabapentin and the hormone drug salmon calcitonin is very poor, which indicates that complicated mechanisms are involved [6][7][8][9][10][11][12]. Clinical studies have shown that treatments targeting the stump of an amputated peripheral limb can effectively relieve CPAP [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that treatments targeting the stump of an amputated peripheral limb can effectively relieve CPAP [ 13 , 14 ]. Our previous studies had also shown that ablation of the neuroma or the stump of the amputated limb with radiofrequency or surgery significantly improves the pain condition of patients [ 7 , 10 ], suggesting an essential role of peripheral nerves in the development of CPAP, but the exact mechanisms of how the neuromas or residual parts of peripheral nerves regulate CPAP still need further study.…”
Section: Introductionmentioning
confidence: 99%